2017
DOI: 10.1002/art.40101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treadmill Exercise on Advanced Osteoarthritis Pain in Rats

Abstract: Objective Exercise is commonly recommended for patients with osteoarthritis (OA) pain. However, whether exercise is beneficial in ameliorating persistent NSAID-resistant ongoing pain associated with advanced OA is unknown. Methods Rats treated with intra-articular monosodium iodoacetate (MIA) or saline underwent treadmill exercise or remained sedentary starting 10 days post-injection. Tactile sensory thresholds and weight bearing were assessed followed by radiographs at weekly intervals. After 4 weeks of exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 59 publications
(105 reference statements)
3
38
0
1
Order By: Relevance
“…CS exerts its anti-inflammatory effects through the inhibition of reactive oxygen species activity or the activation of protein kinases, reducing the synthesis of proteolytic enzymes (mmp-3, mmp-9, and mmp-13), inflammation-related enzymes (pla2, cox-2, nos-2), and proinflammatory factors (il-1β and tnf-α) [ 6 , 7 ]. In this study, administration of CS reduced the expression of mRNA for mmp-13, il-1, and adamts-5 ( p < 0.01), which concurs with previous [ 32 ] studies.…”
Section: Discussionsupporting
confidence: 93%
“…CS exerts its anti-inflammatory effects through the inhibition of reactive oxygen species activity or the activation of protein kinases, reducing the synthesis of proteolytic enzymes (mmp-3, mmp-9, and mmp-13), inflammation-related enzymes (pla2, cox-2, nos-2), and proinflammatory factors (il-1β and tnf-α) [ 6 , 7 ]. In this study, administration of CS reduced the expression of mRNA for mmp-13, il-1, and adamts-5 ( p < 0.01), which concurs with previous [ 32 ] studies.…”
Section: Discussionsupporting
confidence: 93%
“… 13 , 24 , 62 , 120 , 137 , 160 More recently, these behavioral effects have been replicated in exercise models of treadmill running, voluntary wheel running and resistance training as well as in pain models of noninflammatory muscle pain, neuropathic pain, arthritic pain, and glutamate-induced pain. 1 , 6 , 16 , 47 , 58 , 93 , 106 , 107 , 147 Specifically, 8 weeks of voluntary running wheel activity blocked the production of hyperalgesia in a model of noninflammatory muscle pain. Naloxone administered systemically or directly into the periaqueductal gray (PAG) or the rostral ventral medial medulla (RVM), 2 brain locations important in endogenous opioid system, blocked these analgesic effects, whereas systemic injection of naloxone methiodide, a peripherally acting opioid antagonist, had no effect suggesting the central but not peripheral effects of exercise on mediating the endogenous opioid system 16 (Fig.…”
Section: Central Mechanism Of Exercise-induced Analgesiamentioning
confidence: 95%
“…Exercise has also shown to be beneficial for pain relief in less widely studied pain models including osteoarthritis, 1 , 38 incisional pain model, 29 , 30 inflammatory pain model, 45 , 76 , 86 , 125 complex regional pain syndrome, 106 intervertebral disk degeneration (IDD), 101 immobilization-induced pain, 33 , 112 chronic stress-induced pain, 132 ischemia and reperfusion, 128 glutamate-induced pain, 107 and experimental autoimmune encephalomyelitis 7 , 110 (Tables 1 and 2 ). Although behavioral data are important for demonstrating the analgesic effects of exercise, understanding the mechanisms through which physical activity is producing these effects will be beneficial for future development of therapeutic targets for pain reduction.…”
Section: Models Of Exercise-induced Analgesiamentioning
confidence: 99%
“…Exercise is the most commonly recommended intervention in osteoarthritis because surgeries such as total knee replacement may not be optimal in younger populations with osteoarthritis due to its expensive cost and side effects [3,12]. A recent meta-analysis indicated that running has protective effects against knee joint surgery in OA; moreover, exercise also unmasked the protective and pain-alleviating effects [13,14]. Similarly, we observed that the TE group demonstrated less expression of c-fos than the CON7 group.…”
Section: Resultsmentioning
confidence: 99%